Retrospective Analysis of Cardiovascular Effects of FES Cycling in People with Complete and Incomplete Spinal Cord Injury - Percze-Mravcsik Mariann; Fodor Amelita; Radeleczki Balázs; Fehér Melinda; Cserháti Péter; Klauber András; Laczkó József; Zólyominé Botzheim Lilla (JOURNAL OF CLINICAL MEDICINE, 2026)
Background: Globally, over 15 million people live with spinal cord injury (SCI), which often leads to permanent motor impairment. In these cases, functional electrical stimulation (FES) can generate muscle forces and active movements in affected body parts, enabling patients to perform cycling tasks using their own paralyzed legs. Incomplete spinal cord injuries are more prevalent than complete injuries and FES cycling can be performed in both cases. However, differences in its effects between the two groups remain to be further investigated. Our objective is to compare the effects of FES-assisted cycling on blood pressure, heart rate, and power output in patients with incomplete (iSCI) versus complete (cSCI) spinal cord injuries. We aim to provide comparative data currently missing from existing research. Methods: Thirty-two patients (20 iSCI, 12 cSCI), completed at least ten FES cycling training sessions. Each session consisted of 30 min of cycling on a MOTOmed Viva2 cycle-ergometer (Reck GMBH, Betzenweiler, Germany) equipped with a multi-channel electrical stimulator. The outcome measures were assessed in each session four times: before and after the session, and approximately at the 10th and 20th minutes. Statistical analyses compared mean arterial pressure (MAP), heart rate (HR), average and peak power output between the two groups. Results: Regarding within session differences, the iSCI group maintained significantly higher MAP than the cSCI group at all measurement points. HR patterns also differed significantly, showing higher values in the iSCI group at the second and third measurement points. On the course of the sessions in iSCI patients, average and peak power output increased significantly from the first to the tenth session. In cSCI patients the average power output was nearly constant throughout the ten sessions. Conclusions: Patients with iSCI and cSCI show different cardiovascular adaptations, and increasing FES cycling power output indicates that patients with incomplete injuries can achieve greater improvements even after ten training sessions.